COMPARATIVE EVALUATION OF THE EFFECTIVENESS OF DIFFERENT METHODS FOR THE CARIES-DIAGNOSIS OF OCCLUSAL SURFACES OF THE FIRST PERMANENT MOLARS - Nedana Georgieva; Krasimir Hristov; Nataliya Grancharova (Peytchinski Publishing, 2022)
Aim: Comparative evaluation of the diagnostics of the occlusal surface between light-induced fluorescence (SoproLife camera) and the accepted international system for the diagnosis of caries ICDAS II. Materials and methods: 150 first permanent molars were examined in 50 patients in the age group 6-9 years. The results from the studied occlusal surfaces by light fluorescence (SoproLife "day light" and "blue light" 405 nm) and direct visual observation (ICDAS II codes) were compared using a correlation coefficient. Results: A high identity is reported between the two diagnostic methods - correlation coefficient= 0.97 (using Spearman's rank correlation). Conclusion: SoproLife camera eliminates the risk of "overdiagnosis", it is a comparable and reliable method for the detection of initial occlusal carious lesions. Both methods show identical advantages in terms of their diagnostic effectiveness in initial occlusal carious lesions.